2014
DOI: 10.15640/ijgws.v2n3a6
|View full text |Cite
|
Sign up to set email alerts
|

Performance in Mathematics and Science Subjects: A Gender Perspective for Selected Primary Schools in Rural and Urban Tanzania

Abstract: Since the 2000, Tanzania is striving to eliminate gender inequality in the education system. As such, the gender gap in enrolment is closing in primary education. Yet, gendered performance remains a challenge. Using data from Primary School Leaving Examination results for the period between 2007 and 2011, and from qualitative methods, this paper examined trends and factors for poor performance in Mathematics and Science subjects with a gender perspective. Two schools from rural and two from urban areas were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The population of this study comprised the standard seven students in the Government primary schools in Botswana. In order to identify the differences between the performance of male and female students in schools (Kabote et al, 2014;Rahmawati & Ummah, 2020;Mutua & Oyoo, 2020), two schools located in the rural areas and two schools located in the urban areas were purposively selected. Thereafter, a simple random sampling method was used to select an equal number of male and female students (n=25) from each of the four sampled schools.…”
Section: Population and Samplingmentioning
confidence: 99%
“…The population of this study comprised the standard seven students in the Government primary schools in Botswana. In order to identify the differences between the performance of male and female students in schools (Kabote et al, 2014;Rahmawati & Ummah, 2020;Mutua & Oyoo, 2020), two schools located in the rural areas and two schools located in the urban areas were purposively selected. Thereafter, a simple random sampling method was used to select an equal number of male and female students (n=25) from each of the four sampled schools.…”
Section: Population and Samplingmentioning
confidence: 99%
“…In 2003, males outperformed females in science, which was also the case in TIMSS 1999and 1995(Gonzales et al, 2004. Kabote, Niboye, and Nombo (2014),found that girls' performance was higher than boys in some periods in mathematics and science. Zarrett, and Eccles cited in Larson, Stephen, Bonitz and Wu (2014), based on a large sample in the United States, provided evidence that girls had higher science grades than boys in grades 1 through 12.…”
Section: Subjectmentioning
confidence: 99%
“…This could result from parental pressure leading to gifted female perfectionism struggling based on Ryckman and Peckham (1987) with STEM gifted females' scant ability and confident perceptions they hold when nominated for gifted programs. Similarly, gender disparities in STEM exist in Tanzania (Kabote et al, 2014).…”
Section: Introductionmentioning
confidence: 99%